2022
DOI: 10.1007/s11669-022-00963-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Ti-Rich Part of the Ti-Al-Nb System—Part I: Low-Temperature Phase Equilibria Between 700 and 900 °C

Abstract: Precise knowledge of the phase equilibria in the Ti-Al-Nb system between 700 and 900 °C is of crucial importance for the urgently needed improvement of TiAl-based turbine materials already in industrial use to achieve further energy savings. As a result of the occurrence of the two ternary intermetallic phases ωo (“Ti4NbAl3”) and O (“Ti2NbAl”), which form in the solid state just in the range of the application-relevant temperatures, the phase relations are very complex and not well studied. In the present inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…x o ). [34] Such an isolated (bTi,Nb) o phase field has been previously reported by Hellwig et al [12,13] , Li et al [11] , and Eckert et al [14] at 1000 °C. All authors report the same three tie-triangles phase field is found matches in most cases.…”
Section: The Isolated (Btinb) Phase Fieldmentioning
confidence: 53%
See 4 more Smart Citations
“…x o ). [34] Such an isolated (bTi,Nb) o phase field has been previously reported by Hellwig et al [12,13] , Li et al [11] , and Eckert et al [14] at 1000 °C. All authors report the same three tie-triangles phase field is found matches in most cases.…”
Section: The Isolated (Btinb) Phase Fieldmentioning
confidence: 53%
“…% measured at 900 °C for alloy B1. [34] This assumption is supported by the observation that alloy B1 at 1000 °C no longer contains the (aTi) phase, which is more and more displaced by the growing (bTi,Nb) phase field as the temperature increases. For the isothermal sections at 1000 and 1100 °C in Fig.…”
Section: The (Ati) Solid Solutionmentioning
confidence: 88%
See 3 more Smart Citations